A POLITENESS PRINCIPLES ANALYSIS ON THE ASSERTIVE SPEECH ACT IN OBAMA担 SPEECH:PULANG KAMPUNG NIH - Fuji Muliawati, - (2012)
As the 44th President of America, Barrack Obama is hoped to be able to save some global problems such as global crisis, terrorism, and the relationship between America and Muslims. Thus, many people have watched all of his activities regarding to those issues, particularly when he paid state visits to the Muslim's countries. This study entitled "A Politeness Principles Analysis on the Assertive Speech Act in Obama's speech 'Pulang Kampung Nih' " investigates the politeness strategies that President Obama used in his speech "Pulang Kampung Nih" and media responses in perceiving President Obama's speech. The data were taken from the President Obama's speech transcription retrieved from thejakartapost.com and some media responses, The Jakarta Post, Koran Tempo, and Republika which were published on November 9th and 11th, 2010. This study employs a descriptive qualitative method by applying Searle's speech act theory and Leech's politeness principles. The results of the study show there are 4 maxims found in the assertive utterances of President Obama's speech: agreement (63.2%), approbation (19.6%), modesty (12.3%), and sympathy (4.9%). There are two local media, The Jakarta Post and Koran Tempo whom have positive reactions on the President Obama's speech while Republika has a negative reaction toward President Obama's speech. Based on the findings, it appears that the politeness strategies which were used by President Obama were intended to gain more support and reliance from Indonesian people particularly the Muslims.